SP10.2.5 It SOCS: Surgical On-Call Simulation for final year Medical Students. (28th October 2021) - Castelhano, Rute; Gurung, Pratha; Win, Khine Myat; Waters, Christopher; Coleman, Nichola; Scheneiders, Hannah
Abstract: Introduction: Simulation is a well-known method of effectively teaching Medical students. Surgical simulation is a gap within the curriculum, especially Surgical on-call simulations. To improve this, we ran simulation sessions designed to replicate a General Surgery themed on-call shift that junior doctors should be able to manage. We aimed to improve confidence in clinical prioritisation and confidence in being an on-call Junior doctor, managing the most common on-call surgical tasks. Method: Groups of 3-4 final year Medical students participated in a 2 hour-long simulated "on-call" shift, throughout the hospital. There were 8 scenarios, which ranged from prescribing to acute clinical scenarios. Students were given bleeps and were called at set times. They had to receive/give handovers and prioritise tasks according to clinical importance. A debrief following the session focussed on prioritisation and highlighted key learning points. The students completed a pre- and post-session questionnaire as assessment. Results: The percentage of students who felt confident or very confident in the following domains were compared pre- and post-simulation respectively: confidence in clinical prioritisation (17% vs 86%); confidence in prescribing medication (0% vs 14%); confidence in escalation to seniors (33% vs 71%). 87.5% of the participants felt the session was an effective way to learn how to prioritise clinical tasks, and 100% felt this an effective way to learn about common General Surgical queries whilst on-call. Conclusion: This project demonstrates how simulation is also effective in improving confidence in prioritisation and knowledge within clinical practice, especially surgery.